Digital in-line holography for microscopic applications - Singh, Vijay Raj (2011)
Lensless digital holographic microscope (DHM) is presented for the study of transparent micro objects in three dimensions. A highly diverging beam replaces the conventional microscope objectives to provide the desired magnification. Direct evaluation of the phase information from single hologram makes digital holography a most attractive tool in optical metrology. We successfully implement DHM for the applications of “microholes inspection” and “microfluid analysis”. The amplitude and phase contrast images of microholes are numerically reconstructed and ompared with the conventional optical microscopic images. The direct evaluation of phase information gives the 3-D profile of microholes. Furthermore, the change in the refractive index of microfluid occurred by Brownian motion of particles inside a microchannel is studied. Two digital holograms are recorded corresponding to different states of particles motion, the subtracted phase gives the change in optical path length.